Tingkat Diversifikasi Usaha Tani di Daerah Hulu, Tengah, dan Hilir Daerah Irigasi Mambal - WIJAYANTI, PUTU UDAYANI; DJELANTIK, AAA WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Business Diversification of Farmregions in the Upstream, Midstream, and Downstream Regional Irrigation Mambal Diversification of farming is one of the main programs of agricultural development . Program development of diversification of farming in paddy fields is one of the strategies in an effort to stabilize farm income , expansion of employment opportunities and poverty reduction  (Pakpahan , 1990) . Seeing the importance of diversification for the stability of farmers 'income , it is interesting to study how to diversify farming in Mambal Irrigation Area, ( the upstream, midstream and downstream ) and their effects on farmers' income. The specific purpose of this study was to determine the level of farm diversification in the upstream, midstream , and downstream in the flow of irrigation Mambal farm diversification and determine the effect on the income of farmers in the upstream, midstream , and downstream in the flow of irrigation Mambal . The location determination is done intentionally ( purposive ) . The population in this study are all farmers who diversify his farming business .. population is three Subak is Ayung Buduk , Sembung , and Canggu . Then a total of 30 farmers selected proportionally according to the third area of the water control system , so it can be said to represent the entire population, which in this study serve as a peasant family research unit . Analysis of the data used in this research is the analysis of qualitative data is used to determine the field conditions and constraints encountered , as well as farmers' perceptions of diversification and quantitative analysis is used to determine the level of diversification and income . Results from this study was the influence of diversification of the income of farmers in the research area , as well as the absence of barriers in the irrigation water.
Keywords: diversification; farming; farmers; revenue; irrigation